Effect of Asset Structure and Firm Size on Capital Structure (Case Study on Food and Beverage Companies on the Indonesian Stock Exchange) - Feni Feni; Burhanuddin Burhanuddin; Guasmin Guasmin (Universitas Muhammadiyah Palu, 2021)
The calculation results obtained by using multiple linear regression model analysis shows that the asset structure and company size simultaneously or simultaneously have a positive and significant effect on the capital structure. This is supported by the F-count value of 24,957 at a significance level of 0.000 which is smaller than 0.05, which means that the F-count value is greater than the F-table value, which is 24.957 > 3.134. Asset structure partially has a negative and significant effect on capital structure. This is supported by the t-count value of -4.813 at a significance level of 0.000 which is smaller than 0.05 which means that the t-count value is smaller than the t-table value, namely -4.813 <1.994. Firm size partially positive and significant effect on capital structure. This is supported by the t-count value of 4.922 at a significance level of 0.000 which is smaller than 0.05, which means that the t-count value is greater than the t-table value, namely 4.922 > 1.994.